PROFESIONALISME HAKIM DALAM PENYELESAIAN PERKARA PERDATA ISLAM DI PENGADILAN AGAMA PROVINSI BANTEN - Karmawan Karmawan (Institut PTIQ Jakarta, 2019)
This study aims to analyze the professionalism of judges in religious courts in Banten province. Then this study also examines judges' decisions in accordance with the 1945 constitution based on Pancasila to realize a prosperous, safe, peaceful and orderly life order in the life of the people. In order to realize such a way of life and guarantee equality of citizens' position in the law, efforts are needed to uphold justice, truth, and legal certainty that are able to protect the community. In the context of upholding the law and justice of Islamic civil cases in the Banten provincial court, professionalism of judges is needed as a condition for judges to implement decisions in accordance with the values of truth and responsibility as fair judges. Professional judges can provide guidance for many people depending on the professionalism of the judge. For this reason, Islamic Shari'ah has placed the position of judge as a very noble position, to which he is given the freedom to do jihad in enforcing law and justice.